Generalized and classical almost periodic solutions of Lagrangian systems convex on a compact set - Zakharin, S. F.; Parasyuk, I. O. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
By using the variational method, we establish sufficient conditions for the existence of generalized Besicovitch almost (quasi)periodic solutions and classical quasiperiodic solutions of natural Lagrangian systems with force functions convex on a compact set.